WE-FG-207A-01: Introduction to Dedicated Breast CT - Early Studies - Vedantham, S. (Medical physics (Lancaster), 2016)
Mammography-based screening has been a valuable imaging tool for the early detection of non-palpable lesions and has contributed to significant reduction in breast cancer associated mortality. However, the breast imaging community recognizes that mammography is not ideal, and in particular is inferior for women with dense breasts. Also, the 2-D projection of a 3-D organ results in tissue superposition contributing to false-positives. The sensitivity of mammography is breast-density dependent. Its sensitivity, especially in dense breasts, is low due to overlapping tissue and the fact that normal breast tissue, benign lesions and breast cancers all have similar “densities”, making lesion detection more difficult. We ideally need 3-D imaging for imaging the 3-D breast. MRI is 3-D, whole breast ultrasound is 3-D, digital breast tomosynthesis is called 3-D but is really “pseudo 3-D” due to poor resolution along the depth-direction. Also, and importantly, we need to be able to administer intravenous contrast agents for optimal imaging, similar to other organ systems in the body. Dedicated breast CT allows for 3-D imaging of the uncompressed breast. In current designs, the patient is positioned prone on the table and the breast is pendant through an aperture and the scan takes approximately 10 seconds [O’Connell et al., AJR 195: 496–509, 2010]. Almost on the heels of the invention of CT itself, work began on the development of dedicated breast CT. These early breast CT systems were used in clinical trials and the results from comparative performance evaluation of breast CT and mammography for 1625 subjects were reported in 1980 [Chang et al., Cancer 46: 939–46, 1980]. However, the technological limitations at that time stymied clinical translation for decades. Subsequent to the landmark article in 2001 [Boone et al., Radiology 221: 657–67, 2001] that demonstrated the potential feasibility in terms of radiation dose, multiple research groups are actively investigating dedicated breast CT. The development of large-area flat-panel detectors with field-of-view sufficient to image the entire breast in each projection enabled development of flat-panel cone-beam breast CT. More recently, the availability of complimentary metal-oxide semiconductor (CMOS) detectors with lower system noise and finer pixel pitch, combined with the development of x-ray tubes with focal spot dimensions similar to mammography systems, has shown improved spatial resolution and could improve visualization of microcalcifications. These technological developments promise clinical translation of low-dose cone-beam breast CT. Dedicated photon-counting breast CT (pcBCT) systems represent a novel detector design, which provide high spatial resolution (∼ 100µm) and low mean glandular dose (MGD). The CdTe-based direct conversion detector technology was previously evaluated and confirmed by simulations and basic experiments on laboratory setups [Kalender et al., Eur Radiol 22: 1–8, 2012]. Measurements of dose, technical image quality parameters, and surgical specimens on a pcBCT scanner have been completed. Comparative evaluation of surgical specimens showed that pcBCT outperformed mammography and digital breast tomosynthesis with respect to 3D spatial resolution, detectability of calcifications, and soft tissue delineation. Major barriers to widespread clinical use of BCT relate to radiation dose, imaging of microcalcifications, and adequate coverage of breast tissue near the chest wall. Adequate chest wall coverage is also technically challenging but recent progress in x-ray tube, detector and table design now enables full breast coverage in the majority of patients. At this time, BCT has been deemed to be suitable for diagnostic imaging but not yet for screening. The mean glandular dose (MGD) from BCT has been reported to be between 5.7 to 27.8 mGy, and this range is comparable to, and within the range of, the MGD of 2.6 to 31.6 mGy in diagnostic mammography. In diagnostic studies, the median MGD from BCT and mammography were 12.6 and 11.1 mGy, respectively [Vedantham et al., Phys Med Biol. 58: 7921–36, 2013]. Moreover, in diagnostic imaging of the breast the location of the lesion is known and therefore characterization and not detection is by far the primary consideration. The role of bCT is particularly compelling for diagnostic imaging of the breast because it may replace in part the multiple mammographic views of the breast under vigorous compression. Other non-screening potential applications of bCT include the assessment of response to neoadjuvant therapy [Vedantham et al., J Clin Imaging Sci 4, 64, 2014] and pre-surgical evaluation. Learning Objectives: 1. To understand the metrics used to evaluate screening and diagnostic imaging 2. To understand the benefits and limitations of current clinical modalities 3. To understand how breast CT can improve over current clinical modalities 4. To note the early attempts to translate breast CT to the clinic in 1970s-1990s 5. To understand the recent developments in low-dose cone-beam breast CT 6. To understand the recent developments in photon-counting breast CT 7. To understand the radiation dose, clinical translation, and recent developments in diagnostic imaging with breast CT Supported in part by NIH grants R21 CA134128, R01 CA128906 and R01 CA195512. The contents are solely the responsibility of the authors and do not reflect the official views of the NIH or the NCI.; S. Vedantham, Funding sources: Supported in part by NIH/NCI grants R01 CA128906 and R01 CA195512. The contents are solely the responsibility of the authors and do not reflect the official views of the NIH/NCI. Disclosures: Research collaboration with Koning Corporation, West Henrietta, NY. Conflicts of Interest: J. Boone, This research was supported in part by NIH grant R01CA181081; W. Kalender, WK is founder and CEO of CT Imaging GmbH Erlangen, Germany.; A. Karellas, NIH R21 CA134128, R01 CA128906, and R01 CA195512 and Research collaboration with Koning Corporation.